A. \(\frac{1}{9}.\)
B. \(-1\)
C. \(10\)
D. \(\frac{9}{8}.\)
C
\(\begin{array}{l}
\lim \frac{{x + 1 - \sqrt {5x + 1} }}{{x - \sqrt {4x - 3} }} = \frac{{\left( {{x^2} - 3x} \right)\left( {x + \sqrt {4x - 3} } \right)}}{{\left( {{x^2} - 4x + 3} \right)\left( {x + 1 + \sqrt {5x + 1} } \right)}}\\
= \lim \frac{{x\left( {x + \sqrt {4x - 3} } \right)}}{{\left( {x - 1} \right)\left( {x + 1 + \sqrt {5x + 1} } \right)}} = \frac{{3\left( {3 + 3} \right)}}{{2\left( {4 + 4} \right)}} = \frac{9}{8}\\
\Rightarrow T = 2a - b = 10
\end{array}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247